Pemberdayaan Ekonomi yang Inklusif dan Berkelanjutan: Kemandirian UKM Penyandang Disabilitas di Bekasi - Surya Bintarti; Anggi Muhammad Rifai; Novi Fitria Hermiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service program focuses on the economic empowerment of people with disabilities at the Independent Disability Shelter (RUMSIDISMA) Bekasi by strengthening the capacity of culinary MSMEs that still face various obstacles, such as limited production accessibility, low managerial performance, minimal product innovation, and weak digital marketing. Through a comprehensive approach that includes business management training, product innovation, digital marketing, intensive mentoring, and the application of technology such as websites and digital content marketing, this program aims to improve production quality, expand market access, strengthen branding, and encourage inclusive economic independence. All activities are designed to align with the SDGs, IKU, and Asta Cita, with measurable output targets such as improving MSME performance, creating branding designs, creating promotional content, strengthening marketing strategies, and scientific publications, so as to be able to realize business sustainability and improve the welfare of the disability community in a real way.